Frequency of Age-Appropriate Vaccination in Children Till 15 Months of Age Admitted at the Aga Khan Hospital, Karachi, Pakistan - Aiza Mustafa, Anum Mustafa, Manoj Kumar, Rozina Iqbal, Ali Faisal Saleem, Alina Mustafa, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of age-appropriate vaccination till 15 months of age at Aga Khan Hospital, Karachi Pakistan. Study design: Cross-sectional study Place and Duration: Inpatient department of the Aga Khan University Hospital from Nov 2019 to Nov 2020 Methodology: All children admitted to the pediatric ward and fulfilling the inclusion criteria were enrolled. A predesigned proforma was used to collect data on the basic demographics of children and parents, their socioeconomic status, parental education, occupation, and vaccination status. The age-appropriate vaccination was defined as children who had received the vaccination, according to their age as per the expanded program of immunization (EPI) schedule of Pakistan. All collected data were analyzed using SPSS version 23. Results: Out of 350 admitted children, 222 (63.4%) were males and 128 (36.6%) were females. Most of the children were vaccinated (95.7%), while 4.3% were not vaccinated. Among vaccinated children, 63.7% had not received age-appropriate vaccination, and only 127 (36.3%) had age-appropriate vaccination. Statistically, the employment status of mothers (p=0.001) and educational level of mothers (p=0.001) and fathers (p=0.001) were significantly associated with age-appropriate vaccination in children of age up to 15 months. Conclusion: Despite having a high vaccination coverage rate, the proportion of age-appropriate vaccination was lower. The factors associated with age-appropriate vaccination were the employment status of the mother and the educational status of the parents. Vaccination programmes should work on identified risk factors in order to improve age-appropriate vaccination coverage. Keywords: Age appropriate vaccination, immunization, vaccination card